(untitled) (Journal of Food and Dietetics Research, 2024)
Poor menstrual hygiene knowledge, practices, dietary patterns during menstruation increase the risk of reproductive health issues and mental stigma. Despite being a global problem, there is a significant lack of knowledge and many misconceptions about menstrual hygiene among women of all ages, particularly in rural areas. This study aims to assess the knowledge, practices, and dietary patterns related to menstrual hygiene among rural women in Salem, Tamil Nadu. The findings will help policymakers, NGOs, and planners to take effective initiatives. This cross-sectional survey, conducted from December 2023 to January 2024, assessed menstrual hygiene knowledge, practices, and dietary patterns among rural women in Salem, Tamil Nadu. Using convenient sampling, 71 participants were initially recruited, and after excluding incomplete responses, 70 completed surveys were analyzed. Female research staff conducted door-to-door interviews using structured questionnaires in English and Tamil. A pilot test with 10 participants refined the questionnaire. Participants were women aged 18-55. Data were analyzed using SPSS for statistical validation. Majority were aged 31-40, with schooling up to the school level, employed, earning Rs. 5,001-10,000 monthly, living in nuclear families with 3-4 members. While age and education influenced menstrual knowledge, factors like occupation and income did not. Menstrual practices were notably engaged, but not significantly predicted by demographic factors. Dietary patterns varied across occupations. Overall, targeted interventions are needed to improve menstrual health knowledge and practices among rural women, considering demographic and dietary influences. The study reveals the nuanced influence of demographic, socioeconomic, and dietary factors on menstrual health knowledge and practices. While age and education notably affect menstrual knowledge, other factors do not significantly explain menstrual practices. However, dietary patterns stand out as influential, suggesting the need for deeper exploration into how diets impact menstrual hygiene.